2016
DOI: 10.1098/rspb.2015.2838
|View full text |Cite
|
Sign up to set email alerts
|

Stickleback embryos use ATP-binding cassette transporters as a buffer against exposure to maternally derived cortisol

Abstract: Offspring from females that experience stressful conditions during reproduction often exhibit altered phenotypes and many of these effects are thought to arise owing to increased exposure to maternal glucocorticoids. While embryos of placental vertebrates are known to regulate exposure to maternal glucocorticoids via placental steroid metabolism, much less is known about how and whether egg-laying vertebrates can control their steroid environment during embryonic development. We tested the hypothesis that thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…Additionally, developmental effects can occur without direct exposure of offspring to maternal glucocorticoids 38,39 . For example, stickleback embryos are able to buffer themselves from exogenous manipulations of cortisol by actively transporting cortisol out of the egg via ATP-binding cassette transporters 69,71 . This suggests that the effects of maternal predator exposure on offspring behavior [72][73][74] , physiology 75 and embryonic gene transcription 76 in threespine stickleback are not mediated solely by embryonic exposure to maternal cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, developmental effects can occur without direct exposure of offspring to maternal glucocorticoids 38,39 . For example, stickleback embryos are able to buffer themselves from exogenous manipulations of cortisol by actively transporting cortisol out of the egg via ATP-binding cassette transporters 69,71 . This suggests that the effects of maternal predator exposure on offspring behavior [72][73][74] , physiology 75 and embryonic gene transcription 76 in threespine stickleback are not mediated solely by embryonic exposure to maternal cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…The return of all elevated cortisol deposits back to control levels by 48 hpf (hatch) illustrates the importance of maintaining low cortisol levels during this early developmental window. While the mechanism(s) is unclear, a recent study suggested a role for ATP-binding cassette transporters in the rapid cortisol clearance in threespine stickleback ( Gasterosteus aculeatus ) embryos40. Another possibility is the enzyme 11βHSD2, which converts cortisol to inactive cortisone and contains putative glucocorticoid response elements (GRE) in its promoter region41.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol has been detected in both fertilised and unfertilised eggs of numerous species, including white sturgeon Acipenser transmontanus Richardson 1837 (Simontacchi et al, ), Mozambique tilapia Oreochromis mossambicus (Peters 1852) (Hwang & Wu, ), O. mykiss (Auperin & Geslin, ), D. labrax , Japanese flounder Paralichthys olivaceus (Temminck & Schlegel 1846) (de Jesus et al, ), chum salmon Oncorhynchus keta (Walbaum 1792) (de Jesus & Hirano, ), yellow perch Perca flavescens (Mitchill 1814) (Jentoft et al, ) and three‐spinned stickleback Gasterosteus aculeatus (L. 1758) (Paitz et al, ). Owing to inter‐specific variation, the quantity of cortisol in eggs varies between 1 and 600 ng g −1 , as reviewed in Sopinka et al ().…”
Section: Sampling Matrices To Extract Cortisolmentioning
confidence: 99%
“…The regulation probably occurs in ovaries in direct link with the level of 11bHSD2 (Faught et al, ), an enzyme that allows conversion of cortisol to cortisone, its physiologically inert metabolite. Once in the eggs, the cortisol is also actively excreted by the ATP‐binding cassette (ABC) transporters that clears the steroid (Paitz et al, ). The cortisol transmitted from the mother to the offspring was shown to confer positive ( i.e .…”
Section: Sampling Matrices To Extract Cortisolmentioning
confidence: 99%
See 1 more Smart Citation